Analysis of phytochemical variations in dioecious Tinospora cordifolia stems using HPLC/QTOF MS/MS and UPLC/QqQLIT‐MS/MS. Issue 2 (2nd December 2015) - Bajpai, Vikas; Singh, Awantika; Chandra, Preeti; Negi, M. P. S.; Kumar, Nikhil; Kumar, Brijesh
Abstract: Introduction: The stem of dioecious Tinospora cordifolia (Menispermaceae) is a commonly used traditional Ayurvedic medicine in India having several therapeutic properties. Objective: To develop and validate LC‐MS methods for the identification and simultaneous quantitation of various secondary metabolites and to study metabolomic variations in the stem of male and female plants. Methods: Ethanolic extract of stems were analysed by HPLC/ESI‐QTOF‐MS/MS for rapid screening of bioactive phytochemicals. High resolution MS and MS/MS in positive ESI mode were used for structural investigation of secondary metabolites. An UPLC/ESI‐QqQLIT ‐MS/MS method in MRM mode was developed and validated for the simultaneous quantitation of five bioactive alkaloids. Results: Identification and characterisation of 36 metabolites including alkaloids, sesquiterpenes and phytoecdysteroids were performed using LC‐MS and MS/MS techniques. The bioactive alkaloids such as jatrorrhizine, magnoflorine, isocorydine, palmatine and tetrahydropalmatine were successfully quantified in male and female plants. The mean abundances of magnoflorine jatrorrhizine, and oblongine were significantly (P  < 0.05) higher in male plants while mean abundances of tetrahydropalmatine, norcoclaurine, and reticuline were significantly ( P  < 0.05) higher in female plants. Conclusions: Phytochemicals in the stem of male and female Tinospora cordifolia showed significant qualitative and quantitative variations. LC‐MS and MS/MS methods can be used to differentiate between male and female plants based on their chemical profiles and quantities of the marker bioactive alkaloids. This chemical composition difference was also evident during vegetative stage when there were no male and female flowers. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : LC‐MS and MS/MS based method for rapid qualitative and quantitative determination of phytoconstituents in the male and female stem of dioecious T. cordifolia were developed. Significant qualitative and quantitative differences in some of the detected phytoconstituents in between male and female stem were observed. This method can be utilized for quality control and making gender distinction in dioecious plants even under vegetative state.